Ustavnosodna presoja v zvezi s sindikalno svobodo - Korpič-Horvat, Etelka (Delavci in delodajalci, 2012)
Under ZUstS (Constitutional Court Act), representative trade unions in Slovenia have direct access to the Constitutional Court which is unusual in comparison to the regulations in other countries. Trade unions can initiate a review of constitutionality of a regulation or of a general legal act issuedfor the purpose of implementing public mandates before the Constitutional Court. According to the Constitutional Court, collective agreements can neither be regarded as general acts for exercising public mandate, nor as legal provisions in this sense. However, there are two criteria to be met: firstly, the respective trade union must have status of a representative trade union for the respective activity field or profession forthe entire state, and secondly, it must be evident from the motion that the review of constitutionality of the acts in question is necessary because workers rights are being threatened.
Keywords: pravno varstvo; sindikati; ustavna sodišča